Cognitive-perceptual deficits and symptom correlates in first-episode schizophrenia - Riaan M. Olivier; Sanja Kilian; Bonginkosi Chiliza; Laila Asmal; Petrus P. Oosthuizen; Robin Emsley; Martin Kidd (South African Journal of Psychiatry, 2017)
Background: Thought disorder and visual-perceptual deficits have been well documented, but their relationships with clinical symptoms and cognitive function remain unclear. Cognitive-perceptual deficits may underscore clinical symptoms in schizophrenia patients.